Jasmonate-Sensitivity-Assisted Screening and Characterization of Nicotine Synthetic Mutants from Activation-Tagged Population of Tobacco (Nicotiana tabacum L.) - Yin, Guoying; Wang, Wenjing; Niu, Haixia; Ding, Yongqiang; Zhang, Dingyu; Zhang, Jie; Liu, Guanshan; Wang, Sangen; Zhang, Hongbo (Frontiers in Plant Science, 2017)
Nicotine is a secondary metabolite that is important to the defense system and commercial quality of tobacco (Nicotiana tabacum L.). Jasmonate and its derivatives (JAs) are phytohormone regulators of nicotine formation; however, the underlying molecular mechanism of this process remains largely unclear. Owing to the amphitetraploid origin of N. tabacum, research on screening and identification of nicotine-synthetic mutants is scarce. Here, we describe a method based on JA-sensitivity for screening nicotine mutants from an activation-tagged population of tobacco. In this approach, the mutants were first screened for abnormal JA responses in seed germination and root elongation, and then the levels of nicotine synthesis and expression of nicotine synthetic genes in the mutants with altered JA-response were measured to determine the nicotine-synthetic mutants. We successfully obtained five mutants that maintained stable nicotine contents and JA responses for three generations. The method is simple, effective and low-cost, and the finding of transcriptional changes of nicotine synthetic genes in the mutants shows potentials for identifying novel regulators involved in JA-regulated nicotine biosynthesis.